Forecasting Car Demand in Indonesia with Moving Average Method - Fuad Dwi Hanggara (Journal of Engineering Science and Technology Management (JES-TM), 2021)
The automotive industry is an industry that requires a long process and high manufacturing costs. improper can have fatal consequences if not planned properly will cause financial losses. Production planning using statistical tools such as statistical process control can control the right amount of production according to customer demand. Part of the statistics that makes planning for future production planned is forecasting. Precise production quantities require the specialized abilities of technicians experienced in forecasting. The approach used in forecasting uses a quantitative approach using production data, and sales data of the Gabungan Industri Kendaraan Bermotor Indonesia 2020. The use of the Moving Average method in forecasting will determine the number of production limits so that excess production can be avoided, and the automotive industry in Indonesian has many opportunities to develop its production.